Creating Enduring Customer Value. (November 2022) - Sheth, Jagdish N.; Uslay, Can
Definition precedes measurement. The authors define and discuss value, customers and processes to create value. To do so, they distinguish between three business philosophies (product-centric, competition-centric and customer-centric), three types of customers (user, payer and buyer) and three primary types of value (performance, affordability and service) based on these customers' preferences. They introduce and give examples of 10 unique ways of creating value for customers and conclude with research questions for creating enduring customer value.